Quantitative Cryo-TEM Reveals New Structural Details of Doxil-Like PEGylated Liposomal Doxorubicin Formulation - Rickard Nordström; Lin Zhu; Johan Härmark; Yael Levi-Kalisman; Erez Koren; Yechezkel Barenholz; Genia Levinton; Dima Shamrakov (MDPI AG, 2021)
Nano-drugs based on nanoparticles (NP) or on nano-assemblies as carriers of the active pharmaceutical ingredient (API) are often expected to perform better compared to conventional dosage forms. Maximum realization of this potential though requires optimization of multiple physico-chemical, including structural and morphological, parameters. Meaningful distributions of these parameters derived from sufficient populations of individual NPs rather than ensemble distributions are desirable for this task, provided that relevant high-resolution data is available. In this study we demonstrate powerful capabilities of the up-to-date cryogenic transmission electron-microscopy (cryo-TEM) as well as correlations with other techniques abundant in the nano-research milieu. We explored Doxil®-like (an anticancer drug and the first FDA-approved nano-drug) (75-100 nm) PEGylated liposomes encapsulating single doxorubicin-sulfate nano-rod-crystals (PLD). These crystals induce liposome sphere-to-ellipsoid deformation. Doxil® was characterized by a multitude of physicochemical methods. We demonstrate, that accompanied by advanced image-analysis means, cryo-TEM can successfully enable the determination of multiple structural parameters of such complex liposomal nano-drugs with an added value of statistically-sound distributions. The latter could not be achieved by most other physicochemical approaches. It seems that cryo-TEM is capable of quantitative description of individual liposome morphological features, including meaningful distributions of all structural elements, with averages that correlate with other physical methods. Here it is demonstrated that such quantitative cryo-TEM analysis is a powerful tool in determining what is the optimal drug to lipid ratio in PLD, which is found to be the drug to lipid ratio existing in Doxil®.